Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The problem I am working on is to find the where the curve intersects itself, using the parametric equations.

These are: $x=t^2-t$ and $y=t^3-3t-1$

For the graph to intersect itself, there must be two distinct t-values, $a$ and $b$, that when plugged into the parametric equations, produce the same output. These two t-values create two ordered-pairs that are the same.

My system of equations: $a^2-a=b^2-b$ and $a^3-3a-1=b^3-3b-1$.

I solved for $a$, but am not sure if I did it correctly: $a(a-1)=b^2-b$ then either $a=b^2-b$ or $a-1=b^2-b$. I would then have two values that I have to test. When I plugged in $a$, I ended up with a 6-degree polynomial, did I do something wrong?

share|cite|improve this question
up vote 3 down vote accepted

Well, $\,xy=\alpha\beta\,$ doesn't necessarily means $\,x=\alpha\,\,\vee\,\,x= \beta\,$ , of course. Form a quadratic in $\,a\,$ and solve:

$$a^2-a=b^2-b\Longrightarrow a^2-a+b-b^2=0\Longrightarrow \Delta=1-4(b-b^2)=(2b-1)^2\Longrightarrow$$


If $\,a=b\,$ we're done, otherwise take $\,a=1-b\,$ and substitute into the second equation:

$$a^3-3a-1=b^3-3b-1\Longrightarrow 1-3b+3b^2-b^3-3+3b=b^3-3b\Longrightarrow$$

$$0=2b^3-3b^2-3b+2=(b+1)(2b^2-5b+2)\Longrightarrow b=-1\,,\,2\,,\,\frac{1}{2}$$

Thus, we have the solution:

$$t=-1\,,\,t=2\Longrightarrow (x,y)=(2,1)$$

Note that the other two possibilities give us the same $\,t\,$!

share|cite|improve this answer
@EMACK: Another nice similar problem can be found here, – Babak S. Nov 28 '12 at 12:46
There is an easier way of finding a, without using baskara. $$a^2-a+b^2-b=(a+b)(a-b)-(a-b)=0$$ then since the solution $a=b$ is trivial we can consider $a$ diferent from $b$ and take the $a-b$ out of the equation. $$a+b-1=0$$ $$a=1-b$$ – Ivan Lerner Nov 28 '12 at 13:56
Nice way +1.... – DonAntonio Nov 28 '12 at 14:07
@IvanLerner How do we $a=b$, don't they have to be two distinct t-values? And if $a=b$ is true, then wouldn't be have $(a+b)\cdot 0-0=0$? Why can you just "take out" the $(a-b)$? – Mack Dec 3 '12 at 17:15
That is exactly why I assumed $a$ is different than $b$. If they were equal we could not take it out, because what I meant by taking out was $$(a+b)(a-b)-(a-b)=(a-b)(a+b-1)=0$$ Dividing everything by $(a-b)$ gives us $a+b-1=\frac{0}{(a-b)}$ The right side is only possible if $(a-b)$ is different than zero. Thats why, since we are looking for $a$ different than $b$, we can "take it out". If $a=b$ thenyour equation is correct and we don't get any new information, so I just ruled that out. – Ivan Lerner Dec 3 '12 at 20:28

$\large a^2-a=b^2-b$
$\large \left(a-\frac{1}{2}\right)^2=\left(b-\frac{1}{2}\right)^2$
$\large \left|a-\frac{1}{2}\right|=\left|b-\frac{1}{2}\right|$
$\large a,b=\frac{1}{2}\pm x, \ \ x>0$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.